(3GdefXhe hGdefKhQ aj eLGdS GdUOhQs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s
(3ChdgG (B:s
(3GdMeO ddg MeO GdTGcQjf CeG HYO , agPG GLed ef GdeLGdS ChVMJ ajgG CUhdkG ef cdGe GdCFeI s
(3BNQgG (B:s
(3hCeI aGWeI GdRgQG HfJ Cgd GdCUWaG habOe Cgd GdUOb hGdhaG hNGJe GdQSd hGdCfHjGA s
(3HgG fXGe GdJYbjHIs
(3QJHg GdeDda Ydi SHYI hSHYjf eLdSkGs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
Keywords: (3GdCOHs